The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsami.1c06152
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Interfacial Energy Bands for Synthesis of Photoluminescent 0D/2D Coupled MOF Heterostructure with Enhanced Selectivity toward the Proton-Exchange Membrane

Abstract: Engineering of the interface for tuning the structural, functional, and electronic properties of materials via the formation of heterostructure composites exhibits immense potential in the current research scenario. This study reports a novel ternary composite synthesized by decoration of zero-dimensional Pd nanoparticles (NPs) and two-dimensional (2D) graphite oxide (GO) sheets in the UiO-66 metal−organic framework (MOF). A mixed matrix membrane was fabricated by incorporating this composite in the SPEEK poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Influencing properties by tuning the interfacial structures of composites is a promising strategy. In 2021, Mandal et al 143 modified GO and Pd nanoparticles onto UiO-66 to form a composite material, which was then used as a filler to composite with SPEEK to synthesize a hybrid membrane. GO contains a variety of hydrophilic functional groups (carboxyl, hydroxyl, epoxy, etc.…”
Section: Mofs/speek Pemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influencing properties by tuning the interfacial structures of composites is a promising strategy. In 2021, Mandal et al 143 modified GO and Pd nanoparticles onto UiO-66 to form a composite material, which was then used as a filler to composite with SPEEK to synthesize a hybrid membrane. GO contains a variety of hydrophilic functional groups (carboxyl, hydroxyl, epoxy, etc.…”
Section: Mofs/speek Pemsmentioning
confidence: 99%
“…(C) Possible interaction between SPEEK and UiO‐66/Pd‐ graphite oxide (GO). Reproduced with permission from Das et al 143 . Copyright 2021, American Chemical Society…”
Section: Mofs‐based Pems For Pemfcmentioning
confidence: 99%
“…Das et al dispersed GO in DMF by ultrasonic wave to obtain uniform and stable slurry, then introduced UiO-66 framework, added ZrCl 4 and ultrasonic treatment, acidified with HCl, and added BDC. [157] The film was cast on a flat glass plate, dried and annealed, then cooled and immersed in deionized water. Morphological analysis of the composite membrane showed that a uniform and defect-free membrane was formed on the sulfonated poly ether ketone ether (SPEEK) membrane substrate, and the composite was uniformly distributed.…”
Section: D Mof@gomentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] However, research on the construction of these materials is still in its infancy and needs to be further expanded and improved. [35][36][37][38][39][40] Constructing well-defined MOF/MOF heterointerfaces using traditional synthetic methods, such as solvothermal, hydrothermal and one-pot method, is challenging, as precise control at the atomic and molecular levels is difficult to achieve. However, it is feasible to achieve controllable fabrication of MOF heterostructures through hierarchical assembly on a host substrate or seed crystal, [41] which allows for customization of components and structures at both the micro and macro levels.…”
Section: Introductionmentioning
confidence: 99%
“…[27–34] However, research on the construction of these materials is still in its infancy and needs to be further expanded and improved. [ 35–40 ]…”
Section: Introductionmentioning
confidence: 99%